Aquifer pollution by metal-antibiotic complexes: Origins, transport dynamics, and ecological impacts - Dipak Baral; Ajaya Bhattarai; Narendra Kumar Chaudhary (Ecotoxicology and Environmental Safety)
Aquifer pollution by metal-antibiotic complexes is a rising environmental and public health concern owing to their enhanced mobility and persistence in groundwater. The purpose of this review is to examine the origins, transport dynamics, and ecological impacts of complexes formed through interactions between metal ions and antibiotics in agricultural runoff, pharmaceutical effluents, and wastewater discharge. Metal-antibiotic complexes are more resistant to degradation and are more soluble than their components. This complicates the conventional water purification efforts. These complexes disrupt microbial ecosystems, facilitate the spread of antibiotic-resistance genes, and negatively affect aquatic organisms. The entry of pollutants into drinking water sources poses notable health risks, including chronic exposure to contaminants and the emergence of antibiotic-resistant pathogens. This review emphasizes both preventative and remedial strategies to mitigate these impacts. Preventative measures emphasize the regulation of antibiotic and metal use in agriculture and industry and promote green chemistry alternatives. Remediation approaches include advanced treatment technologies such as membrane filtration, oxidation, and bioremediation. Integrated management practices and ongoing monitoring were discussed to address this complex issue. To protect water quality and public health, metal-antibiotic complexes in aquifers require stringent regulatory measures, innovative treatment solutions, and heightened public awareness. This review highlights the importance of coordinated efforts to prevent and remediate the emerging pollution problem.